2018
DOI: 10.1021/acs.chemmater.7b03529
|View full text |Cite
|
Sign up to set email alerts
|

Temperature Dependence of Structural and Transport Properties for Na3V2(PO4)2F3 and Na3V2(PO4)2F2.5O0.5

Abstract: Among polyanionic-based electrode materials developed for Na-ion batteries, one of the most promising families turns out to be Na 3 V 2 (PO 4 ) 2 F 3-y O y (0 ≤ y ≤ 2). Here, we present the influence of the oxygen substitution for fluorine on the structural and transport properties of Na 3 V 2 (PO 4 ) 2 F 3-y O y , as a function of temperature, through the comparison of the two compositions y = 0 and y = 0.5. An orderdisorder phase transition is observed whatever the content in oxygen, in relation with changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 24 publications
1
21
0
Order By: Relevance
“…A much higher energy barrier is calculated for Na hops between neighboring rings, of the order of 0.6 eV and above 43 . These hops are required for macroscopic diffusion; in fact, recently the activation energy for Na conduction in Na3V2(PO4)2F3 was measured by Impedance Spectroscopy and reported to be 680 meV (or even greater) 44,45 , in good agreement with the calculations.…”
Section: Please Do Not Adjust Marginssupporting
confidence: 77%
“…A much higher energy barrier is calculated for Na hops between neighboring rings, of the order of 0.6 eV and above 43 . These hops are required for macroscopic diffusion; in fact, recently the activation energy for Na conduction in Na3V2(PO4)2F3 was measured by Impedance Spectroscopy and reported to be 680 meV (or even greater) 44,45 , in good agreement with the calculations.…”
Section: Please Do Not Adjust Marginssupporting
confidence: 77%
“…This was recently observed in the mixed valence phase Na3V2(PO4)2F2.5O0.5 for which a significant improvement of the electronic conductivity has been evidenced compared to that of the pure V 3+ phase (i.e. Na3V2(PO4)2F3) 36…”
Section: High Voltagementioning
confidence: 57%
“…This work is part of a series of studies conducted in our groups and dealing with vanadyltype defects in vanadium fluoride phosphate materials (LiVPO4F 7,8,17 and Na3V2(PO4)2F3 27,36 ). The combination of advanced characterizations by diffraction and spectroscopy allowed an in-depth understanding of the LiVPO4F1-yOy phases, from their long range average structure to their local one.…”
Section: Resultsmentioning
confidence: 99%
“…Bianchini et al revealed the detailed phase diagram during Na extraction and structural distortion using high angular and intensity resolution synchrotron radiation diffraction. Broux et al investigated the influence of the oxygen substitution for fluorine on the structural and transport properties of Na 3 V 2 (PO 4 ) 2 F 3 as a function of temperature. Yu group investigated the intrinsic ionic and electronic conductivities, as well as the chemical diffusion coefficient of Na + of Na 3 V 2 (PO 4 ) 2 F 3 .…”
Section: Vanadium Phosphatesmentioning
confidence: 99%